2014
DOI: 10.1016/j.jmb.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Antiparasitic Activity of a Mercaptoacetamide Derivative That Inhibits Histone Deacetylase 8 (HDAC8) from the Human Pathogen Schistosoma mansoni

Abstract: Schistosomiasis, caused by the parasitic flatworm Schistosoma mansoni and related species, is a tropical disease that affects over 200 million people worldwide. A new approach for targeting eukaryotic parasites is to tackle their dynamic epigenetic machinery that is necessary for the extensive phenotypic changes during the life cycle of the parasite. Recently, we identified S. mansoni histone deacetylase 8 (smHDAC8) as a potential target for antiparasitic therapy. Here, we present results on the investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 48 publications
1
70
1
Order By: Relevance
“…In a second study, an inhibitor bearing a mercaptoacetamide (1a) warhead ( Figure 4B) showed specificity for smHDAC8 over hHDAC8 (Table 1) [87]. The structure in complex with smHDAC8 revealed a specific binding mode of its warhead to the catalytic zinc and a flipping-in of the smF151 side chain, whereas smH292 was not involved in inhibitor binding ( Figure 5F) [87].…”
Section: Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…In a second study, an inhibitor bearing a mercaptoacetamide (1a) warhead ( Figure 4B) showed specificity for smHDAC8 over hHDAC8 (Table 1) [87]. The structure in complex with smHDAC8 revealed a specific binding mode of its warhead to the catalytic zinc and a flipping-in of the smF151 side chain, whereas smH292 was not involved in inhibitor binding ( Figure 5F) [87].…”
Section: Reviewmentioning
confidence: 95%
“…The structure in complex with smHDAC8 revealed a specific binding mode of its warhead to the catalytic zinc and a flipping-in of the smF151 side chain, whereas smH292 was not involved in inhibitor binding ( Figure 5F) [87]. Both linkerless hydroxamates and mercaptoacetamide induced apoptosis in cultured worms.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Moreover, observed resistance and reduced efficiency of praziquantel in laboratory strains have prompted the search for alternative therapeutic strategies. [20][21][22][23][24][25][26][27] Trypanosomiasis, which represents several diseases caused by parasites of the genus Trypanosoma, is also of interest. 5,27,29 This disease, which is much arguably the most important disease of man and domesticated animals, accounts for over 8 million reported annual cases globally, especially in the tropical regions of Latin America and Africa.…”
Section: Introductionmentioning
confidence: 99%